REDUCING SERVICE WAITING TIME OF READY MEDICINE IN A GENERAL HOSPITAL - Limanjaya, Felix
Indonesian Ministry of Health had regulated standards for various healthcare services that must be adhered by all hospitals. This study mainly focuses on ready (packed) medicine in pharmacy sector and had chosen a general hospital in Bandung as the subject. The Ministry of Health set thirty minutes as the maximum duration for serving the required ready medicine to the patients. After performing direct observation and collecting information for eight months, the data indicated that, serving process generally exceeded the limit given. To diminish the time taken for the whole process, in depth analysis of the duration of each activity involved in the process is necessary. The staff allocated in the pharmacy changed each day resulted in varying value in the control chart. Hence, this study picked peak hour period with the most patient. Next, the duration data from this period were used to analyze each activity deeper. For each activity, the data must include only in-control data and the distribution type of the data had to be identified. After identifying the distribution and obtaining in-control data, the mean of each activity is recorded. The mean duration of each activity was summed up which result in total in-control serving process duration. It was found that the total in-control serving process duration still exceeded thirty minutes. This indicates that the normal performance of the staffs did not meet the standard, hence defects were present. To analyze this issue, simulation was done. The simulation showed that there were significant waiting times between activities, which indicated lack of staffs in the processes. Initially, staffs were allocated evenly every day. Several scenarios were then tried in the simulation to prove that rescheduling of personnel will positively contribute to the issue. The simulation required distribution type for each activity, which had already been identified before. After performing the simulation, it was found that one scenario where allocating more staffs at peak hour and providing different break time reduced the time significantly. Therefore, this shows that rescheduling the shift of staffs diminishes the time taken for the whole process of serving the ready medicine. In conclusion, by having a more appropriate distribution of staffs throughout the day will help pharmacy of the hospital to achieve the standard set by the Ministry of Health which in turn will increase customers’ satisfaction.